PEA‐15 facilitates EGFR dephosphorylation via ERK sequestration at increased ER–PM contacts in TNBC cells. Issue 9 (18th March 2015) - Shin, Miyoung; Lee, Kyung-Eun; Yang, Eun Gyeong; Jeon, Hyesung; Song, Hyun Kyu
Abstract : Phosphoprotein enriched in astrocytes of 15kDa (PEA‐15) is known to sequester extracellular signal‐regulated kinase (ERK) in the cytoplasm, inhibiting tumorigenesis of human breast cancer cells. Here, we describe how PEA‐15 expression affects the dephosphorylation of epidermal growth factor receptor (EGFR) through endoplasmic reticulum (ER)–plasma membrane (PM) contacts in MDA‐MB‐468, triple‐negative breast cancer (TNBC) cells. The increased intracellular calcium concentration resulting from increased cytoplasmic phosphorylated ERK facilitates movement of ER‐anchored calcium sensors to the PM. The driving force of trans‐localization of calcium‐dependent proteins enhances the contact between the activated EGFR and ER‐localized phosphatase, PTP1B. Consequently, our findings suggest a mechanism underneath the facilitation of EGFR dephosphorylation by cytoplasmic PEA‐15 expression inside TNBC cells, which may be one of the dynamic mechanisms for down‐regulation of activated EGFR in cancer cells. Abstract : PEA‐15 sequestrates phosphorylated ERK1/2 in the cytoplasm and increases intracellular calcium concentration. Contact between the plasma membrane and endoplasmic reticulum is triggered by overexpression of PEA‐15. PEA‐15 influences dephosphorylation of EGFR by ER‐localized PTP1B in MDA‐MB‐468 TNBC cells.